Macular hole closure with minimal or no posturing after macular hole surgery - Awan, Amer; Muid, Javeria; Hafeez, Aiman (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find the success rate of idiopathic and traumatic Macular hole (MH) with minimal/ no posturing after Macular Hole (MH) surgery. Study Design: Interventional case series. Place and Duration of Study: Ophthalmology clinic, Shifa International Hospital Islamabad from July 2017 to December 2018. Material and Methods: Nineteen eyes of 19 patients with either idiopathic or traumatic MH were included in the study. All the patients with decreased vision due to any other cause or previous failed MH surgery were excluded. Their preoperative swept source OCT scans were done and MH was categorized according to size of MH. 27 gauge 3 ports pars plana vitrectomy, inner limiting membrane peel and gas (Hexafluoroethane) tamponade was performed in all the patients. No posturing was advised for small MH while minimal prone positioning was advised for medium and large sized MH. Results: All the patients had closed MH at post-operative day 1 except one patient who showed decrease in size of hole after surgery. There was significant improvement in vision in all patients from mean preoperative visual acuity of 0.8 logarithm of minimum angle of resolution (Range 0.3 to 2.0) to mean post-operative visual acuity of 0.3 logarithm of minimum angle of resolution (Range 0.1 to 0.5). On an average 4 lines improvement in visual acuity occurred. Conclusion: This study confirms MH closure within 24 hours on the basis of swept source OCT. Prone positioning does not appear to affect closure of small MH. For medium and large sized MH, minimal posturing is needed.